THE FABLED ADVENTURE OF O ANO DE 1993: MEMORIES OF THE WORLD TO COME - Antonietti Lopes, Tania Mara [UNESP] (Univ Fed Rio De Janeiro, Fac Letras, 2017)
Based on our reading of O ano de 1993 (1975), by Jose Saramago, and using an interpretative framework stemming from Surrealism and dystopian science fiction novels, we propose an analysis that allows us to draw parallels between this book and the epic tradition, given that, despite the lack of a single epic hero, or glorious actions or memorable feats (among other typical elements of the genre), it is still possible to observe in the narrated poem a chain of extraordinary events that provoke surprise and wonder-albeit great disillusionment in certain moments-as they relate the adventure of man (as hero and hangman) on Earth. Through the interpretative exercise we propose, we hope to demonstrate our hypothesis about the circularity of extraordinary traits that characterize most of Saramago's fiction, present since the author's formative period.
Keywords: O ano de 1993; Jose Saramago; surrealism; dystopia